2023
DOI: 10.3389/fpsyg.2023.1143359
|View full text |Cite
|
Sign up to set email alerts
|

The Kenny music performance anxiety inventory (K-MPAI): Scale construction, cross-cultural validation, theoretical underpinnings, and diagnostic and therapeutic utility

Abstract: I commenced my academic exploration of music performance anxiety in a study with opera chorus artists from Opera Australia in 2004. I subsequently postulated a new theory of the aetiology of music performance anxiety and began the development of the Kenny Music Performance Anxiety Inventory (K-MPAI) to assess the hypothesized theoretical constructs underpinning its diverse clinical presentations. I proposed a new definition of music performance anxiety in 2009 and revised the item content of the K-MPAI from 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 73 publications
(124 reference statements)
1
5
0
Order By: Relevance
“…One of the main reasons for that is the absence of FOA studies in music with a learning paradigm in an application-oriented educational setting. Concerning on-stage musical performances in performance under pressure contexts, the research situation manifests as tighter due to a long tradition of multidisciplinary investigations in relation to anxiety and stress in high-pressure performing settings from psychology, sports, and music, e.g., the growing field of music performance anxiety research (for current reviews, see Fernholz et al, 2019 ; Osbourne and Kirsner, 2022 ; Kenny, 2023 ). However, studies showed that dealing with music-specific high-pressure challenges is highly individual and diverse, and depends on multiple factors (see, e.g., Buma et al, 2015 ; Oudejans et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the main reasons for that is the absence of FOA studies in music with a learning paradigm in an application-oriented educational setting. Concerning on-stage musical performances in performance under pressure contexts, the research situation manifests as tighter due to a long tradition of multidisciplinary investigations in relation to anxiety and stress in high-pressure performing settings from psychology, sports, and music, e.g., the growing field of music performance anxiety research (for current reviews, see Fernholz et al, 2019 ; Osbourne and Kirsner, 2022 ; Kenny, 2023 ). However, studies showed that dealing with music-specific high-pressure challenges is highly individual and diverse, and depends on multiple factors (see, e.g., Buma et al, 2015 ; Oudejans et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…A higher score represents higher levels of MPA as well as psychological distress ( Kenny, 2011 ). The questionnaire has been validated and used in numerous research studies and is available in several languages ( Kenny, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…Once the content of the proposed design is validated, a pilot study is conducted to evaluate its effectiveness in reducing MPA. For this purpose, pre-and post-measurements of MPA are carried out using the K-MPAI test [55]. Additionally, post-treatment MPA measurement is complemented with a qualitative evaluation of the program through a participant satisfaction questionnaire designed ad hoc (mixed design).…”
Section: Design and Proceduresmentioning
confidence: 99%
“…To assess the level of MPA experienced by the participants, the Kenny music performance anxiety inventory (K-MPAI) [55] was used in its complete version, as it is the psychometric record shared by most studies in recent research. It is the only instrument developed for this purpose based on a psychological theory, Barlow's triple vulnerability theory [32,68].…”
Section: Dependent Variable (Dv): Perceived Mpamentioning
confidence: 99%
See 1 more Smart Citation